An experimental and numerical investigation of an improved shearing process with different punch characteristics - Gomah, Mahmod (Strojniški vestnik, 2020)
Blanking and piercing shearing processes have been widely used to manufacture workpieces for industrial, commercial and testing purposes. During the operation, the punch is exposed to higher stresses and, due to the cycled contact of opposite surfaces, it can be worn significantly. As its surface directly affects the quality of sheet products and causes some surface defects, its performance plays a significant role. In this study, various tools with different characteristics were investigated for an improved shearing process. First, a novel punch with a hemispherical ball at the centre of its flat face was tested and compared with a conventional one. The process was simulated using ABAQUS/Explicit finite element (FE) program, in which the Johnson-Cook material model with its complementary damage model was used to represent the behaviour of the sheet material. Based on this, an optimum geometry for the proposed punch was determined. Secondly, the wear resistance of TiN, CrN, TiSiN, AlCrN and AlTiN coated punches, produced with physical vapour deposition (PVD) technique, and of the polycrystalline diamond compact (PDC) cutter were compared based on scanning electron microscope (SEM) micrographs after 1000 strokes under dry cutting conditions.
Keywords: fizikalno nanašanje prevleke iz parne faze; geometrija pestiča; Johnson-Cookov model zloma; obraba; physical vapour deposition coating; polycrystalline diamond compact cutters; proces striženja; punch geometry; rezkarji iz polikristaliničnega diamanta; simulacije po metodi končnih elementov; wear